Asas Pacta Sunt Servanda dalam Pembagian Harta Pusaka Berdasarkan Ganggam Bauntuak Iduik Bapadok dalam Masyarakat Adat Minangkabau (Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 2651 K/Pdt/2022) - Salsabila, Anisa (UNES Law Review, 2023)
Modern human life is closelyarelated to legal acts, transactions and agreements. This article reviews the concept of agreementaaccordingy top Articlep 1313 rofpthep Civilp Code, emphasizing that the term "law of agreement" covers all forms of engagement. The definition of agreement, both in the context of customary and civil law, involves legal relationships between individuals or groups with a focus on property law. Along with the development of customary law in Indonesia, there was dualism in land law before Law Number 5 of 1960, which reflected the relationship between legal alliances and land. In the context of the Minangkabau Customary Law Community, the article examines their special position with customary rights as the highest land rights. The matrilineal kinship system in Minangkabau also displays the concept of inheritance which involves material and non-material elements.